PRECIPITAÇÃO E APORTE DE NUTRIENTES EM DIFERENTES ESTÁDIOS SUCESSIONAIS DE FLORESTA ATLÂNTICA, PINHEIRAL - RJ1 - Diniz, Anderson Ribeiro; Pereira, Marcos Gervasio; Balieiro, Fabiano De Carvalho; Machado, Deivid Lopes [UNESP]; Menezes, Carlos Eduardo Gabriel (Universidade Federal de Santa Maria, 2013)
Forest cover has importance within the context of the water balance of a particular site and may alter the mechanism of entry of water and nutrients to the soil surface. The aim of this study was to quantify the net precipitation, interception, addition of nutrients in throughfall and stem flow in a forest in different stages of regeneration of Mata Atlântica: early-stage secondary forest (ESSF), intermediary stage secondary forest (ISSF) and advanced stage secondary forest (AESF). The study was conducted in Pinheiral, Rio de Janeiro state. The data collection was performed during the period of April 2009 to March 2010. The values of incident precipitation, effective precipitation and interception were similar among the three stages evaluated. The AESF area showed higher values of Mg and P in the addition of nutrients from throughfall compared with other areas assessed. The pH of the precipitation incident did not differ among areas, but was higher than the pH of rainfall. The three areas evaluated showed no difference in the addition of nutrients to flow through the trunk. The AESF area showed a trend of higher levels of addition of nutrients from throughfall precipitation and runoff from stemflow.

A cobertura florestal possui importância dentro do contexto do balanço hídrico de determinado local, podendo alterar o mecanismo de entrada de água e nutrientes na superfície do solo. Apresenta-se o resultado de um estudo que visou quantificar a precipitação efetiva, a interceptação e a adição de nutrientes na precipitação interna e no escoamento pelo tronco em um remanescente florestal da Mata Atlântica com diferentes estádios sucessionais: floresta secundária em estádio inicial (FSEI), floresta secundária em estádio médio (FSEM) e floresta secundária em estádio avançado (FSEA). O estudo foi conduzido no município de Pinheiral - RJ, durante o período de abril de 2009 a março de 2010. Os valores de precipitação incidente, precipitação efetiva e de interceptação foram similares entre os três estádios avaliados. A área de FSEA apresentou maiores valores de Mg e P na adição de nutrientes via precipitação interna em relação às demais áreas avaliadas. O pH da água da precipitação interna não diferiu entre as áreas, mas foi mais elevado do que o pH da precipitação total. As três áreas avaliadas não apresentaram diferença quanto à adição de nutrientes via escoamento pelo tronco. A área FSEA apresentou uma tendência de maiores valores de adição de nutrientes via precipitação interna e escoamento pelo tronco.
PRECIPITATION AND NUTRIENT CONTRIBUTION IN DIFFERENT SUCCESSIONAL STAGES OF ATLANTIC FOREST, PINHEIRAL, RIO DE JANEIRO STATE
Keywords: water balance; succession; community ecology; balanço hídrico; sucessão; ecologia de comunidades